English Teachers’ Perception on the Use of Authentic Assessment in EFL Classroom at MA Al-Fatah Palembang - Shalehuddin Al Ayubi; Dian Erlina; Deta Desvitasari (Yayasan Karinosseff Muda Indonesia, 2021)
The aims of the study is aimed to find out English teacher’s perception on the use of authentic assessment and it’s difficulties in EFL classroom. The approach of this study used a qualitative research. One of the qualitative research designs applied in this study was case study design. The participant of this study two of the English teachers of MA Al-Fatah Palembang. The data were collected through interview. The results of this study showed that the use of authentic assessment in EFL classroom at MA Al-Fatah Palembang is very helpful by the teachers in learning process. This research finding consisted of four themes, as follows; the concept of authentic, types of authentic assessment, the steps of authentic assessment and the strengths and weakness of authentic assessment. The teachers basically supported this assessment to implement in English language teaching classroom. However, the teacher found some difficulties during instructional activities such as managing class activity, maintaining consistence scoring, and monitoring student’s work originality. Therefore, the teacher is expected to extent her insight and creativity to improve the quality of the assessment.